Enterprise Architecture Planning for the Transformation of Career Development Center (CDC) Business Processes at Ma’soem University - Nugraha, Muhamad Fahmi; Naasyiah, Rifdah; Maulana, Doni Rizki (International Journal of Mathematics, Statistics, and Computing, 2025)
The Career Development Center (CDC) at Ma’soem University supports students and alumni in preparing for the workforce through services such as counseling, psychological testing, tracer studies, and job vacancy information. However, the absence of an integrated system makes these services less efficient and difficult to manage. This study proposes a centralized information system using the Enterprise Architecture Planning (EAP) approach to support the CDC’s digital transformation. The design includes data, application, and technology architectures aimed at improving service delivery and operational performance. The system development process involves observation, interviews, business process modeling (BPMN), and data structure design (ERD). The result is a system design with key modules supported by secure technological infrastructure. The system is planned to be implemented in stages and is expected to help the CDC operate more effectively and align with the needs of the industrial sector.